¿Why Leeds? (Alternautas, 2024)
The following piece was written by Elisa Martinez Relano in 2023. Inspired by a student-led project exploring past and present solidarities with Latin America, Elisa, now completing an MA in the History of Art and Social History at the University of Leeds, wrote the following text. Her reflection on archival research around Chilean exile in the 1970s takes place in 2023, fifty years after the infamous coup, and is guided by a simple question: how and why would Leeds engage in solidarity activism with a place as seemingly distant as Chile?